A little yellow dog - Mosley, Walter (Serpent's Tail, 1996)
It's 1964, and Easy Rawlins has given up street life, and has a job as a high school janitor. One morning, Easy is seduced by a teacher with a dog. By evening, the teacher is gone, leaving Easy with her dog, and a corpse. A murderer is running loose and a little yellow dog is plotting revenge.